Analisis Faktor Penyebab Kekosongan Obat dan Implementasi Strategi MMSL Berbasis Hospital Information System: : (Studi Kasus RS Gatoel Mojokerto) - Adistya Nugraha F; Imam Shalihin Amin; Nur Ayu Rahmawati; Dian Tri Febriana; Faradian Fajri; Nasrudin Nasrudin; Achmad Zakaria; Herin Mawarti; Renny Padma Prihatini (Pusat riset dan Inovasi Nasional, 2025)
Drug stock-outs are an indicator of pharmaceutical management failure that directly affects patient safety and the quality of hospital services. Gatoel Hospital Mojokerto experienced an increase in the percentage of drug debt from 3.14% in January to 6.20% in July 2025, with 1,607 patients affected. This study aims to identify the factors causing drug stock-outs and formulate preventive strategies through the optimization of the Minimum-Maximum Stock Level (MMSL) system based on the Hospital Information System. A mixed-method approach was used, combining secondary data analysis (January–July 2025) and in-depth interviews. Fishbone analysis was applied to identify root causes, USG analysis to determine priorities, and SWOT analysis to formulate intervention strategies. Priority drug classification was carried out using the ABC-VEN method. The intervention involved implementing an MMSL pilot project for 150 drug items under Pareto category A. The analysis identified six dimensions of stock-out causes: man, materials, methods, machines, measurement, and environment. The highest priority issue was drug demand forecasting based on historical data (USG score: 125). SWOT analysis placed the organization in quadrant II, recommending a Weakness-Opportunities (WO) strategy. MMSL implementation was initiated through the development of SOPs and the entry of 150 priority drug items into the system. Drug stock-outs are caused by multifactorial issues that require systemic intervention. MMSL optimization has the potential to serve as a long-term solution, provided there is expanded coverage, strengthened human resource capacity, and comprehensive system integration.